Data Privacy Governance, Consumer Trust, and Continued Use of E-Wallets in Cambodia: The Mediating Role of Perceived Fairness - Sokha Chan; Trần Văn Nam (Kalam Practica Media, 2026)
E-wallet ecosystems have expanded rapidly in Cambodia, yet sustained use increasingly depends on consumer confidence in how platforms handle personal data. While technical security remains important, consumers also evaluate governance practices such as transparency, consent, and fairness of data use. This study examines how perceived data privacy governance influences continued use intention of e-wallets through consumer trust and perceived fairness. Drawing on privacy calculus and institutional trust perspectives, the model conceptualizes privacy governance as clarity of consent, data minimization, transparency of third-party sharing, and responsiveness to complaints. Survey data were collected from 621 Cambodian e-wallet users who had conducted at least five transactions in the previous month. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used to test direct effects and serial mediation. Results indicate that privacy governance strengthens perceived fairness and consumer trust; fairness also strengthens trust; trust predicts continued use intention. The findings suggest that retention in digital finance depends on governance legitimacy, not only on usability. Practical implications emphasize plain-language disclosures, granular permissions, and visible dispute resolution practices that reduce privacy anxiety and increase long-term engagement.